A Teologia simbólica de Santa Teresa de Lisieux - Alves dos Santos , Josefa (Kairós: Revista Acadêmica da Prainha, 2021)
This present article analyzes the Scientia Amoris in the life and writings of Saint Teresa of Lisieux from the symbol of the lyre, which represents the human heart, and the dynamism of the divine action which is able to transform even a mere child into a great saint. The text derives from a historical-biographical presentation, to then, present the Theresian symbolic theology with its originality and deepen the four dimensions of human love present in the image of the lyre in its capacity of receiving and giving itself through spousal and maternal, filial and fraternal love. Through the life of Saint Teresa of the Child Jesus and the Sacred Face and her doctrine of Spiritual Childhood, she presents the process of purification and sanctification of the human heart within the symbolism of the lyre as a safe and actual path to follow Christ.